PENGEMBANGAN MODEL PELATIHAN INOVATIF UNTUK MENINGKATKAN KOMPETENSI KADER POSYANDU MELALUI SEKOLAH KADER - Supatmi; Erma Pranawati; Eni Purwaningsih; Dian Novita Kumalasari (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2024)
The competence of Posyandu cadres plays a crucial role in supporting the success of Posyandu activities, including community education. Posyandu cadres act as primary service providers and support for the community, enhancing knowledge and skills. The aim of this research is to determine the improvement of Posyandu cadre competence and the key influencing factors. The research design utilizes a one-group pretest-posttest research design. Data collection methods include skills surveys and interviews with cadres, as well as testing. Cadre training is conducted over 10 months with a total of 20 face-to-face meetings and practical sessions at Posyandu.The study was conducted in the Soka hamlet, Seloharjo, Pundong, Bantul, involving 24 respondents. This research employs univariate analysis and bivariate analysis using Spearman rank. The results of the bivariate analysis show that the social environment contributes 0.846 to cadre competence, organizational support contributes 0.682 to cadre competence, and supervision contributes 0.835 to the improvement of cadre competence. Posyandu cadre training positively influences knowledge and skills, leading to improved performance in Posyandu activities. Supervision, organizational support, and the social environment factor into the effectiveness of improving Posyandu cadre competence.